Deacetylative Protocol to Obtain Diastereoselectively α-Fluoro-β-amino-oxindoles via a Mannich-Type Reaction using Aliphatic N-tert-Butanesulfinyl Imines - Blanco-López, Ester; Sirvent, Ana; Lulli, Thomas; Merino, Pedro; Nájera, Carmen; Yus, Miguel; Foubelo, Francisco; Retamosa, María de Gracia; Sansano, José M. (Synthesis, 2025)
The deacetylative reaction of 3-acetyl-3-fluoro-2-oxindoles with a mild base promotes the in situ generation of 3-fluoro-2-oxindole enolates which react with aliphatic N-tert-butanesulfinyl imines via the Mannich-type reaction generating α-fluoro-β-sulfinylamino oxindoles in a diastereoselective way. The orientation of the attack of the enolate to the imine was computationally investigated, and the analysis of the absolute configuration of the resulting products was performed according to vibrational circular dichroism.
Keywords: Oxindoles; Diastereoselective; N-tert-Butanesulfinyl imines; Mannich; VCD; DFT